2014
DOI: 10.1002/nml.21119
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents or Effects of Being a Manager in the Nonprofit, Public, or Private Sector

Abstract: In this correspondence I postulate a complementary consideration to an article recently published in Nonprofit Management & Leadership: “Factors Attracting Individuals to Nonprofit Management over Public and Private Sector Management” (LeRoux and Feeney 2013). The aim of this correspondence is to provide avenues for further research based on an evaluation of the authors’ analysis and their embedded assumptions on causality and interdependency of the variables used. I perform an extended empirical analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…These results are consistent with findings that employees' value preferences, work motivations, and job satisfaction differ between the sectors (Heywood et al, 2002;Lee & Wilkins, 2011;Van der Wal et al, 2008). However, all of these results imply the studied characteristics and incentives neither have actually triggered sorting effects among those who already work in different sectors (Willems, 2014) nor that they will trigger such effects among future applicants. As long as application intentions and job choices remain unstated or unobserved, little is known about preferences for or against public sector employers vis-àvis competitors from other sectors.…”
Section: Literature Review and Hypothesessupporting
confidence: 89%
“…These results are consistent with findings that employees' value preferences, work motivations, and job satisfaction differ between the sectors (Heywood et al, 2002;Lee & Wilkins, 2011;Van der Wal et al, 2008). However, all of these results imply the studied characteristics and incentives neither have actually triggered sorting effects among those who already work in different sectors (Willems, 2014) nor that they will trigger such effects among future applicants. As long as application intentions and job choices remain unstated or unobserved, little is known about preferences for or against public sector employers vis-àvis competitors from other sectors.…”
Section: Literature Review and Hypothesessupporting
confidence: 89%
“…Particular traits of (groups of) public servants might be at the origin of stereotypical associations that citizens conceive about them. For example, a substantial body of literature comparing public servants with employees in the for-profit and nonprofit sectors has shown that public servants can differ substantially with respect to perceptions about job content, work-life balance, job performance, job satisfaction and motivation (Goulet and Frank 2002;Ben-Ner et al 2011;Willems 2014). These differences from other sectors might be the result of self-selection by prosocial, motivated people in this sector, or by socialization when working with like-minded colleagues (Becker and Connor 2005;De Cooman et al 2011).…”
Section: Sources Of Stereotypical Associations About Public Servantsmentioning
confidence: 99%
“…Moreover, socialization processes play an important role in illustrating and exemplifying values through ongoing interaction and communication among organizational members. Prior research has provided evidence on the particular importance of all these mechanisms in nonprofit organizations, thus illustrating how their dedication to values becomes visible through the guiding function of values (Handy & Katz, 1998; LeRoux & Feeney, 2013; Willems, 2014).…”
Section: Dedication To Values As a Particular Characteristic Of Nonpr...mentioning
confidence: 99%